(untitled) (Al-Qamar, 2022)
Before the emergence of Islam women was considered inferior and was given a lower status, but Islam has furnished them with moral, social and family rights. Unfortunately, with the passage of time, they are depriving from their basic rights. Violence is the major problem of all societies of the world. East and west both have been impacted through it. Now civilized societies are trying to stop violence against women, for it they are making laws. But still laws regarding women rights have not been implemented. In this research article it has been tried to find out causes of violence against women, main kinds of violation and its remedies in the light of teaching of Islam and contemporary laws have been discussed in a scholarly manner. This article consists of: